Analisis Pengaruh Upah Minimum, Pendapatan Asli Daerah, Tenaga Kerja dan Pertumbuhan Ekonomi terhadap PDRB Perkapita Provinsi Jambi - Etik Winarni; Yolanda Sari; Muhammad Amali (Universitas Batanghari Jambi, 2023)
Per capita income and economic growth are the most important signs of achieving the development of a region. If economic development replaces an undeveloped economic structure with human capital and investment, the prosperity of the population or per capita income will increase. Economic growth can be assessed from the amount of PDRB per capita as part of development, in people's welfare and economic growth is one of the components for increasing people's welfare as measured by PDRB per capita. This study aims to analyze how the influence of UMP, PAD, labor and economic growth on PDRB per capita in Jambi Province. Data analysis in this study used multiple linear regression using the SPSS program. The dependent variable (Y) of this study is PDRB per capita, while the independent variable (X) is the Provincial Minimum Wage, Regional Original Income, Labor, Economic Growth. The results of this study Variable (X1) UMP has a positive and significant effect on PDRB per capita or accepts Ho. The coefficient value of 0.393 shows a positive result, where when the minimum wage increases by 1%, there will be an increase in PDRB per capita of 0.393 percent. Variable (X2) PAD has no negative and insignificant effect on PDRB per capita or rejects Ho. A coefficient value of 0.003 indicates a negative result, which means that if each change in PAD is 1%, there will be a decrease in PDRB Per Capita by 0.003 percent. Variable (X3) TK has no negative and insignificant effect on PDRB per capita or rejects Ho. A coefficient value of 0.044 indicates a negative result, which means that for every 1% growth in the workforce, there will be a decrease in per capita PDRB by 0.044 percent. Variable (X4) Economic Growth has a positive and significant effect on PDRB Per Capita or accepts Ho. The coefficient value of 0.003 shows a positive result, where when the change in economic growth increases by 1%, there will be an addition of 0.003 percent PDRB per capita.